Regulatory T-Cells Mediate IFN-α-Induced Resistance against Antigen-Induced Arthritis - Chenna Narendra, Sudeep; Chalise, Jaya Prakash; Biggs, Sophie; Kalinke, Ulrich; Magnusson, Mattias (Frontiers in Immunology, 2018)
Objective: CD4+FoxP3+CD25+ regulatory T-cells (Tregs) are important for preventing tissue destruction. Here we investigate the role of Tregs for protection against experimental arthritis by IFN-α. Methods: Arthritis was triggered by intra-articular injection of methylated bovine serum albumin (mBSA) in wt mice, Foxp3DTReGFP+/- mice (allowing selective depletion of Tregs by diphtheria toxin) and CD4-Cre+/- IFNA1R flox/flox mice (devoid IFNAR-signalling in T-cells) earlier immunized with mBSA, with or without treatment with IFN-α or the indole-amine 2, 3 dioxygenase (IDO)-metabolite Kynurenine. Tregs were depleted in diphtheria-toxin treated Foxp3DTReGFP+/- mice and enumerated by FoxP3-staining. Suppressive capacity of FACS-sorted CD25++CD4+ Tregs was tested in vivo by adoptive transfer and ex vivo in co-cultures with antigen-stimulated CFSE-stained Tresponder (CD25-CD4+) cells. IDO was inhibited by 1-methyl tryptophan (1-MT). Results: Both control mice and mice devoid of IFNAR-signalling in Thelper cells were protected from arthritis by IFN-α. Depletion of Tregs in the arthritis phase, but not at immunization, abolished the protective effect of IFN-α and Kynurenine against arthritis. IFN-α increased the number of Tregs in ex vivo cultures upon antigen re-call stimulation but not in naïve cells. IFN-α also increased the suppressive capacity of Tregs against mBSA-induced Tresponder cell proliferation ex vivo and against arthritis when adoptively transferred. The increased suppressive activity against proliferation conferred by IFN-α was clearly reduced by in vivo inhibition of IDO at immunization, which also abolished the protective effect of IFN-α against arthritis. Conclusion: By activating IDO during antigen sensitization, IFN-α activates Tregs, that prevent arthritis triggered by antigen re-challenge. This is one way by which IFN-α suppresses inflammation.